Wide-band multiwavelength Brillouin–Raman fiber laser based on feedback optimization - Ahmad, Harith; Al-Alimi, A.W. (Elsevier, 2019)
A multiwavelength Brillouin–Raman fiber laser (BRFL) with a 51-nm wide bandwidth is proposed and demonstrated. The BRFL is configured in a half-open cavity (HOC) design with a variable optical attenuator in the cavity. The BRFL exhibits a 60 % improvement in tunability as compared to a conventional half-open BRFL structure. At a Raman pump power of 1.2 W and 1525 nm Brillouin pump power of 12 dBm, 652 uniform Stokes lines with an average optical signal to noise ratio (OSNR) higher than 40 dB are produced. The generated channels have a total output power of 14.5 dBm and a power fluctuation of 0.5 dB over a period of one hour. In contrast, the conventional HOC shows a lower performance in terms of tuning range, OSNR and Stokes lines count. The 51 nm bandwidth using a single Raman pump laser is, to the best of our knowledge, the widest yet reported. © 2019 Elsevier B.V.